2001
DOI: 10.1007/s12110-001-1013-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between subsistence and age at weaning in “preindustrial” societies

Abstract: Cross-cultural studies have revealed broad quantitative associations between subsistence practice and demographic parameters for preindustrial populations. One explanation is that variationin the availability of suitable weaning foods influenced the frequency and duration of breastfeeding and thus the length of interbirth intervals and the probability of child survival (the "weaning food availability" hypothesis). We examine the available data on weaning age variation in preindustrial populations and report re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
134
2
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(152 citation statements)
references
References 49 publications
12
134
2
4
Order By: Relevance
“…From the comparison of BWPs of skeletal and ethnographic populations, we concluded that weaning ages in nonindustrial human populations have no systematic pattern of variation over time and space during the Holocene. Our results, as well as a metaanalysis of the BWPs reported in ethnographic studies (Sellen and Smay, 2001), have indicated that weaning age did not differ according to subsistence. The increased availability of starchy weaning foods and animal milks produced by agricultural and pastoral activities in ancient populations is assumed to have facilitated early weaning, contributing to shorter birth intervals and increased fertility.…”
Section: Applications Studied Tissuessupporting
confidence: 73%
See 1 more Smart Citation
“…From the comparison of BWPs of skeletal and ethnographic populations, we concluded that weaning ages in nonindustrial human populations have no systematic pattern of variation over time and space during the Holocene. Our results, as well as a metaanalysis of the BWPs reported in ethnographic studies (Sellen and Smay, 2001), have indicated that weaning age did not differ according to subsistence. The increased availability of starchy weaning foods and animal milks produced by agricultural and pastoral activities in ancient populations is assumed to have facilitated early weaning, contributing to shorter birth intervals and increased fertility.…”
Section: Applications Studied Tissuessupporting
confidence: 73%
“…For example, ethnographic studies have indicated that liquids, such as fruits, teas, and cereal gruel with lower protein content are frequently used in the early weaning process in both modern and traditional human populations (WHO, 1998;Sellen and Smay, 2001). However, the d…”
Section: Routing Of Isotopes and Trace Elementsmentioning
confidence: 99%
“…How could increased appetite in the absence of expression of PEGs be reconciled with the theoretical prediction that PEGs increase costs to mothers or their kin? The anthropological literature suggests that humans typically introduced supplemental foods at about six months, with cessation of breastfeeding in the third year [11]. If the onset of hyperphagia is in the second or third year, as envisaged in the two-phase model of PWS, then appetite increased at roughly an age at which our ancestors were being weaned from the breast.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other great apes, human offspring are weaned early, leading to an extended period of dependence on procured resources rather than breast milk (1,4). Although this unique human reproductive pattern is viewed as shortening the interbirth interval and thus increasing fertility (5,6), what is less clear is why humans also grow so slowly during childhood.…”
mentioning
confidence: 99%